Usefulness of NF2 hemizygous loss detected by fluorescence in situ hybridization in diagnosing pleural mesothelioma in tissue and cytology material: A multi-institutional study. (January 2023) - Sa-ngiamwibool, Prakasit; Hamasaki, Makoto; Kinoshita, Yoshiaki; Matsumoto, Shinji; Sato, Ayuko; Tsujimura, Tohru; Kawahara, Kunimitsu; Kasai, Takahiko; Kushitani, Kei; Takeshima, Yukio; Hiroshima, Kenzo; Iwasaki, Akinori; et al.
Highlights: NF2 hemizygous loss (HL, 90%: monosomy) seen in 49–54% of pleural mesothelioma (PM). No CDKN2A homozygous deletion (HD) or NF2 HL in benign mesothelial lesion (BML). [ NF2 HL + BAP1 loss + CDKN2A HD] yields > 95 % sensitivity in distinguishing PM from BML. CDKN2A HD significantly affects overall survival, while BAP1 loss and NF2 HL do not. Abstract: Objectives: BAP1, CDKN2A, and NF2 are the most frequently altered genes in pleural mesotheliomas (PM). Discriminating PM from benign mesothelial proliferation (BMP) is sometimes challenging; it is well established that BAP1 loss, determined by immunohistochemistry (IHC), and CDKN2A homozygous deletion (HD), determined by fluorescence in situ hybridization (FISH), are useful. However, data regarding the diagnostic utility of NF2 FISH in PM is limited. Thus, we performed a multi-institutional study examining the utility of NF2 alterations determined by FISH for diagnosing PM in combination with BAP1 loss and CDKN2A HD. Materials and methods: Multi-institutional PM cases, including 106 surgical and 107 cell block samples as well as 37 tissue cases of benign mesothelial proliferation (BMP) and 31 cell block cases with reactive mesothelial cells (RMC), were collected and analyzed using IHC for BAP1 and FISH for CDKN2A and NF2 . Results: In PM, NF2 FISH revealed hemizygous loss (HL) in 54.7% of tissue cases (TC) and 49.5% of cell block cases (CBC), with about 90% of HL being monosomy. CDKN2A HD or BAP1 loss were detected in 75.5%/65.4% TC or 63.6%/60% CBC, respectively. BMP or RMC showed no BAP1 loss, CDKN2A HD, or NF2 HL. For discriminating PM from BMP, a combination of BAP1 loss, CDKN2A HD, and NF2 HL yielded enhanced sensitivity of 98.1% TC/94.4% CBC. BAP1 loss, CDKN2A HD, or NF2 HL were observed in 69%, 70%, or 58% of epithelioid PM, but in 9%, 91%, or 27% of sarcomatoid PM, respectively. Histotype, histological gradings, and CDKN2A deletion status showed significant differences in overall survival, while BAP1 loss and NF2 HL did not. Conclusion: NF2 HL, consisting predominantly of monosomy, can be detected by FISH in both TC and CBC of PM, and is effective for distinguishing PM from BMP, especially when combined with BAP1 loss and CDKN2A HD.